Answer:
-1/8
Step-by-step explanation:
what is the question can u say?
Answer:
b.
Step-by-step explanation:I think
Answer: Haha I don't know the answer---Wait wait--I know the answer, its Do School and study for it and you'll find out :)
Step-by-step explanation: This is how i figured it out.... I STUDIED
Answer:
Yes, it is true that
is a factor of
.
Step-by-step explanation:
Let us try to factorize ![x^4+3x^3-2x^2-3x+1](https://tex.z-dn.net/?f=x%5E4%2B3x%5E3-2x%5E2-3x%2B1)
![x^4+3x^3-2x^2-3x+1\\\Rightarrow x^4-2x^2+1-3x+3x^3](https://tex.z-dn.net/?f=x%5E4%2B3x%5E3-2x%5E2-3x%2B1%5C%5C%5CRightarrow%20x%5E4-2x%5E2%2B1-3x%2B3x%5E3)
Let us try to make a whole square of the given terms:
![\Rightarrow (x^2)^2-2\times x^2 \times 1+1^2+3x^3-3x\\\Rightarrow (x^2-1)^2+3x^3-3x\\](https://tex.z-dn.net/?f=%5CRightarrow%20%28x%5E2%29%5E2-2%5Ctimes%20x%5E2%20%5Ctimes%201%2B1%5E2%2B3x%5E3-3x%5C%5C%5CRightarrow%20%28x%5E2-1%29%5E2%2B3x%5E3-3x%5C%5C)
--------------
Formula used above:
![a^{2} -2 \times a \times b +b^{2} = (a-b)^2](https://tex.z-dn.net/?f=a%5E%7B2%7D%20-2%20%5Ctimes%20a%20%5Ctimes%20b%20%2Bb%5E%7B2%7D%20%20%3D%20%28a-b%29%5E2)
In the above equation, we had
.
--------------
Further solving the above equation, taking
common out of ![3x^3-3x](https://tex.z-dn.net/?f=3x%5E3-3x)
![\Rightarrow (x^2-1)^2+3x(x^2-1)\\](https://tex.z-dn.net/?f=%5CRightarrow%20%28x%5E2-1%29%5E2%2B3x%28x%5E2-1%29%5C%5C)
Taking
common out of the above term:
![\Rightarrow (x^2-1)((x^2-1)+3x)\\\Rightarrow (x^2-1)(x^2+3x-1)](https://tex.z-dn.net/?f=%5CRightarrow%20%28x%5E2-1%29%28%28x%5E2-1%29%2B3x%29%5C%5C%5CRightarrow%20%28x%5E2-1%29%28x%5E2%2B3x-1%29)
So, the two factors are
.
The statement that
is a factor of
is <em>True.</em>